Implementasi Core Values Dan Employer Branding ASN Dalam Upaya Meningkatkan Kinerja Aparatur Sipil Negara : Studi Kasus Pada Dinas Ketahanan Pangan, Pertanian Dan Perikanan Kota Banjar - Doni Indratno; Enas Enas; Oyon Saryono (Jurnal Riset dan Inovasi Manajemen, 2024)
The core value of ASN BerAKHLAK and employer branding ASN were inaugurated by the President of the Republic of Indonesia on July 27, 2021. Core Value ASN BerAKHLAK stands for Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative. The purpose of launching ASN Core Value is to standardize basic values for all civil servants in Indonesia so that it can become the foundation of a quality, dignified and professional ASN work culture. While ASN's employer branding "Proud to Serve the Nation" is a manifestation of the spirit in providing excellent service to the community. High dedication and professionalism are needed to foster a positive image and increase public satisfaction and trust in the existence of ASN itself. This study aims to describe, know, and describe as well as analyze and explain the stages, obstacles and solutions in the implementation of ASN's core value and employer branding in an effort to improve the performance of the state civil apparatus. The process of this implementation stage uses the theory of Lester and Stewart (Nastia, 2014: 201). In this study, using informants as a source of information and data as well as documentation so that research results were obtained that the implementation of ASN's core value and employer branding in an effort to improve the performance of the state civil apparatus in DKPPP Banjar City had gone well. The results of the study and analysis show that the implementation of the core value and employer branding of ASN in DKPPP Banjar City has gone well.